The Road to Azure Cost Governance : Techniques to Tame Your Monthly Azure Bill with a Continuous Optimization Journey for Your Apps. - Annis, Paola E. (Packt Publishing, Limited, 2022)
Get to grips with Microsoft Azure cost management and gain complete, reliable, and sustainable control of your cloud spend Key Features Explore resource rightsizing and cleanup methods and their implementation Learn key resource usage optimization concepts Understand app optimization and plan for optimized and sustainable cloud native applications Book Description Cloud teams and ICT cost controllers working with Azure will be able to put their knowledge to work with this practical guide, introducing a process model for structured cost governance. The Road to Azure Cost Governance is a must-read if you find yourself facing the harsh reality of monthly cloud costs gradually getting out of control. Starting with how resources are created and managed, everything you need to know in order to track, display, optimize, rightsize, and clean up cloud resources will be tackled with a workflow approach that will leave the choice of operation to you (be it the Azure CLI, automation, logic apps, or even custom code). Using real-world datasets, you'll learn everything from basic cost management to modeling your cloud spend across your technical resources in a sustainable way. The book will also show you how to create a recursive optimization process that will give you full control of spending and savings, while helping you reserve budget for future cloud projects and innovation. By the end of this Azure book, you'll have a clear understanding and control of your cloud spend along with knowledge of a number of cost-saving techniques used by companies around the world, application optimization patterns, and the carbon impact of your cloud infrastructure. What you will learn Use Azure reporting, monitoring, and configurations to model your cloud resources and make costs clearer Discover resource-saving techniques and put them into practice Establish a continuous clean-up and rightsizing process Explore and implement automation to drive recurrent savings Find out how to use Azure Reservations in the best possible way Get started with building cloud native, cost-optimized applications Get to grips with implementing cost- and carbon-aware applications on Azure Who this book is for If you're someone who deals with Azure cloud costs and has a technical background, this book will help you understand and control your cloud spending. This book is for decision-makers, cloud managers, cloud architects, cost controllers, and software solution professionals working with Microsoft cloud services in Azure and looking to build optimized solutions for their enterprise operations.